Replacing Income in Retirement for the Newly Retired: A Distributional Analysis of Gross and Net Replacement Rates - Bender, Keith A. (Journal of Income Distribution®, 2007)
Income replacement after retirement is an increasingly important economic policyarea of social concern. This study examines three different measures of replacementincome, including the effect of taxes on the estimated replacement rates of newretirees in the Health and Retirement Study. An analysis of replacement rates on averageand in different parts of the distribution shows that married, older, and voluntaryretirees have the highest replacement rates and that income from pensions and SocialSecurity still form the majority of retirement income replacement.